2011
DOI: 10.1248/cpb.59.714
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Enantioselective Allylic Substitution with Less Active N- or O-Nucleophiles Catalyzed by Iridium-Complex of Bis(oxazolinyl)pyridine

Abstract: Enantioselective transition metal-catalyzed allylic substitutions have been developed as fundamentally important crosscoupling reactions. [1][2][3][4][5][6][7][8] In general, the heteroatom nucleophiles in these reactions have been largely limited to alkylamines, anilines, carboxylates and phenols. Our laboratory is interested in searching the synthetically useful heteroatom nucleophiles for the synthesis of functionalized allylic compounds (Fig. 1).9) As our successful examples, we have recently reported the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…While its use as a sensitizer of Ln(III) ion luminescence remains scarce, since Pybox was first reported by Nishiyama in 1989, it has been extensively utilized in catalysis. Nishiyama et al showed that Pybox can be synthesized with substituted oxazoline rings and used as a ligand in a Ru(IIII) catalyst for the asymmetric hydrosilylation of ketones . Recent reports of enantioselective catalysis using transition-metal complexes with oxazoline-derivatized Pybox ligands include cross-coupling reactions on racemic halides with aryl zinc reagents, Nazarov cyclizations, asymmetric [3 + 2] cycloadditions of racemic cyclopropanes and aldehydes or alkynes with N -tosylaziridines, carbonyl-ene reactions, aminations, , Negishi cross-coupling, , Mukaiyama-aldol reactions, allylic substitutions with N or O nucleophiles, and copper-catalyzed reduction of secondary amines . Pybox complexes of transition metals have also successfully been immobilized on solid supports to be used in catalytic processes. Pybox complexes of the rare earths have been used in Friedel–Crafts alkylations, Mukaiyama-aldol reactions, , and silylcyanation of aldehydes .…”
Section: Introductionmentioning
confidence: 99%
“…While its use as a sensitizer of Ln(III) ion luminescence remains scarce, since Pybox was first reported by Nishiyama in 1989, it has been extensively utilized in catalysis. Nishiyama et al showed that Pybox can be synthesized with substituted oxazoline rings and used as a ligand in a Ru(IIII) catalyst for the asymmetric hydrosilylation of ketones . Recent reports of enantioselective catalysis using transition-metal complexes with oxazoline-derivatized Pybox ligands include cross-coupling reactions on racemic halides with aryl zinc reagents, Nazarov cyclizations, asymmetric [3 + 2] cycloadditions of racemic cyclopropanes and aldehydes or alkynes with N -tosylaziridines, carbonyl-ene reactions, aminations, , Negishi cross-coupling, , Mukaiyama-aldol reactions, allylic substitutions with N or O nucleophiles, and copper-catalyzed reduction of secondary amines . Pybox complexes of transition metals have also successfully been immobilized on solid supports to be used in catalytic processes. Pybox complexes of the rare earths have been used in Friedel–Crafts alkylations, Mukaiyama-aldol reactions, , and silylcyanation of aldehydes .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the above mentioned addition was highly diastereoselective, the same reaction under identical conditions but in the absence of CeCl 3 resulted in the formation of a small amount of the anti,anti diastereomer of 4 (anti,syn/anti,anti, 80:20). Subsequently, the treatment of anti,syn-4 with zinc in acetic acid at 40 °C gave the N-Cbz-protected amino diol 11 in a very good yield of 85% [20,26]. Next, we investigated the substrate-directed epoxidation that could deliver an oxygen atom from the same side of the double bond as the adjacent hydroxy group [27].…”
Section: Resultsmentioning
confidence: 99%
“…Later the iridium‐pybox catalysis was extended for the regio‐ and stereoselective allyl substitution of nitrogen nucleophiles such as hydroxyl amines, aliphatic and aromatic amines in DCM with CsOH.H 2 O as the optimized base. The reaction also worked well with p ‐methoxy phenol using K 2 CO 3 as the base (Scheme ) …”
Section: Ir‐pyboxmentioning
confidence: 87%